A Mixed Finite Element Method on a Staggered Mesh for Navier-Stokes Equations (Journal of Computational Mathematics, 2021)
In this paper, we introduce a mixed finite element method on a staggered mesh for the numerical solution of the steady state Navier-Stokes equations in which the two components of the velocity and the pressure are defined on three different meshes. This method is a conforming quadrilateral $Q_1× Q_1-P_0$ element approximation for the Navier-Stokes equations. First-order error estimates are obtained for both the velocity and the pressure. Numerical examples are presented to illustrate the effectiveness of the proposed method.
Keywords: Mixed finite element method; Staggered mesh; Navier-Stokes equations; Error estimate.